1978
DOI: 10.1002/1097-0142(197801)41:1<228::aid-cncr2820410131>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The significance of vascular invasion and lymphocytic infiltration in invasive cervical cancer

Abstract: Surgical specimens from 100 patients with stage I B cervical cancer undergoing radical hysterectomy and pelvic lymphadenectomy were reviewed with respect to vascular invasion and lymphoplasmacytic infiltration. Lymph nodes from these patients were classified morphologically according to the criteria proposed by Cottier. Vascular invasion was associated with a significant increase in nodal metastases and tumor recurrence particularly to extrapelvic sites. A marked lymphoplasmacytic infiltrate around tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(34 citation statements)
references
References 19 publications
(3 reference statements)
3
28
0
3
Order By: Relevance
“…Similar findings has been reported by van Nagell et al [11] who showed that when lymphovascular space invasion was present in patients with invasive cervical cancer, the recurrence rate increased from 8% to 34%, and also by Hopkins et al [22] who demonstrated that the presence of lymphovascular space invasion decreased the 5-year survival rate from 98% compared to 88% in patients without lymphovascular space invasion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings has been reported by van Nagell et al [11] who showed that when lymphovascular space invasion was present in patients with invasive cervical cancer, the recurrence rate increased from 8% to 34%, and also by Hopkins et al [22] who demonstrated that the presence of lymphovascular space invasion decreased the 5-year survival rate from 98% compared to 88% in patients without lymphovascular space invasion.…”
Section: Discussionsupporting
confidence: 87%
“…These high-risk factors lowers the 5-year survival rate to 40-58%, and the 5-year survival rate after recurrence drops markedly to less than 10% [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Known factors associated with LNM, such as detection of human papilloma virus by genotyping and LVSI, were not included in the present study (van Nagell et al , 1978; Garzetti et al , 1998). Notably, three of the four patients incorrectly classified as low risk had LVSI on final pathologic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Al analizar la respuesta infl amatoria local, se esperaba encontrar una menor SV en pacientes con un bajo escore en respuesta infl amatoria (mayor respuesta), según lo reportado previamente 14,16,33 , ya que el infi ltrado infl amatorio representa la respuesta del estroma en presencia de neoplasias malignas y son considerados como una expresión de las interacciones entre el sistema inmune del huésped y el tumor 34 , donde el número y tipos de células que componen la respuesta infl amatoria corresponden de manera predominante a macrófagos, linfocitos, célu-las natural killer, eosinófi los y mastocitos, quienes en conjunto están relacionados con la producción local de quimiocinas y otros factores quimiotácticos que aumentan las respuestas en el tumor 35 . En el cáncer de mama 36 , de cuello del útero 37 , gástrico 38 , y cáncer de cabeza y cuello 39 , se ha encontrado una correlación positiva entre un aumento de densidad del infi ltrado infl amatorio y la progresión neoplásica.…”
Section: Discussionunclassified